Three Memoranda of the 21st Dynasty at Deir el-Bahari - Barwik, Mirosław (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
Newly found hieratic graffiti in the temple of Hatshepsut at Deir el-Bahari enable shedding new light on the history of the area in the period of the 21 st Dynasty. Three of them, written in the form of memoranda relating presumably to work done in the area, can be dated to the very end of the pontificate of the high-priest Menkheperre. There are good reasons to relate them to a burial or burials in the neighbouring Bab el-Gasus cache or else to the work done in this tomb at an early stage of its building history.